Characterisation of the in-vivo miRNA landscape in Drosophila ribonuclease mutants reveals Pacman-mediated regulation of the highly conserved let-7 cluster during apoptotic processes - Bernard, Elisa I. M.; Towler, Benjamin P.; Rogoyski, Oliver M.; Newbury, Sarah F. (Frontiers in Genetics, 2024)
The control of gene expression is a fundamental process essential for correct development and to maintain homeostasis. Many post-transcriptional mechanisms exist to maintain the correct levels of each RNA transcript within the cell. Controlled and targeted cytoplasmic RNA degradation is one such mechanism with the 5'-3' exoribonuclease Pacman (XRN1) and the 3'-5' exoribonuclease Dis3L2 playing crucial roles. Loss of function mutations in either Pacman or Dis3L2 have been demonstrated to result in distinct phenotypes, and both have been implicated in human disease. One mechanism by which gene expression is controlled is through the function of miRNAs which have been shown to be crucial for the control of almost all cellular processes. Although the biogenesis and mechanisms of action of miRNAs have been comprehensively studied, the mechanisms regulating their own turnover are not well understood. Here we characterise the miRNA landscape in a natural developing tissue, the Drosophila melanogaster wing imaginal disc, and assess the importance of Pacman and Dis3L2 on the abundance of miRNAs. We reveal a complex landscape of miRNA expression and show that whilst a null mutation in dis3L2 has a minimal effect on the miRNA expression profile, loss of Pacman has a profound effect with a third of all detected miRNAs demonstrating Pacman sensitivity. We also reveal a role for Pacman in regulating the highly conserved let-7 cluster (containing miR-100, let-7 and miR-125) and present a genetic model outlining a positive feedback loop regulated by Pacman which enhances our understanding of the apoptotic phenotype observed in Pacman mutants.